A novel whole-body thermal stress test for monitoring cardiovascular responses in guinea pigs. (April 2023) - Sixtus, Ryan P.; Berry, Mary J.; Gray, Clint L.; Dyson, Rebecca M.
Abstract: Cardiovascular disease is a leading cause of morbidity and mortality worldwide. Stress tests are frequently employed to expose early signs of cardiovascular dysfunction or disease and can be employed, for example, in the context of preterm birth. We aimed to establish a safe and effective thermal stress test to examine cardiovascular function. Guinea pigs were anaesthetized using a 0.8% isoflurane, 70% N2 O mix. ECG, non-invasive blood pressure, laser Doppler flowmetry, respiratory rate, and an array of skin and rectal thermistors were applied. A physiologically relevant heating and a cooling thermal stress test was developed. Upper and lower thermal limits for core body temperature were set at 41.5 O C and 34 O C, for the safe recovery of animals. This protocol therefore presents a viable thermal stress test for use in guinea pig models of health and disease that facilitates exploration of whole-system cardiovascular function. Highlights: We developed a safe, reproduceable and relevant thermal stress test for animals. This test allows whole-system cardiovascular stress monitoring in guinea pigs. This test is safe for use in animals with vulnerable cardiovascular systems.